Modeling of the windings for determining the transient voltages transferred in a power transformer - Ramos Carrión, Jorge (2019)
The present article exposes the development of the research on the modeling of the windings of a power transformer to determine and analyze the transient voltages transferred to the secondary winding when an atmospheric impulse voltage is applied to the primary winding. Each winding is modeled considering its geometric and constructive form by means of concentrated electrical parameters - Resistance, Dielectric Conductance, Series Capacitances, Earth Capacitance, Inductiveness and Mutual Inductance - calculated with conventional formulations, which are incorporated into an integral model of the windings that explains his behavior in front of surges. The analysis is carried out with the support of a software of fast transients in the time domain, being able to demonstrate the utility of the model since it is possible to calculate, inside the windings, the transient voltages propagated and transferred, allowing the study of the stresses dielectrics in the insulation of the windings to improve their dosage and geometry in the design process of the power transformer.